A Case of Bronchoscopic Removal of Aspergilloma in Patients With Non‐Surgical Indications - Tetsuka, Takatoshi; Nakamura, Yusuke; Goto, Yuto; Mikura, Sunao; Yazawa, Nana; Suzuki, Hiromichi; Shimizu, Yasuo; Niho, Seiji (Respirology case reports, 2025)
ABSTRACT A 76‐year‐old man was diagnosed with aspergilloma in the left upper lobe. Due to advanced age and recurring colon cancer, surgery was not an option. The aspergilloma was removed with biopsy forceps. Then, the lesion and sputum were decreased. Bronchoscopic removal can be considered, particularly for patients without surgical indications. We present a case of bronchoscopic removal of an aspergilloma using biopsy forceps. This procedure can be considered as a therapeutic strategy, particularly for patients who are not eligible for surgery.